The ‘Screw Boys’ and the ‘Businessmen’: re-Negotiating Penal Power, Governance and Legitimate Authority Through a Prison Violence Reduction Scheme - Gooch, Kate (The British journal of criminology, 2023)
Drawing on ethnographic and qualitative research, this article explores how both prisoners and staff wield authority in prison and with what effects. It combines legitimacy theory and governance theory to consider the relationship between legitimate and illegitimate governance by prisoners and officers, as well as establishing the limits of prisoner governance in remedying the deficits in State illegitimacy. It is argued that legitimate governance by prisoners (in the form of peer-support roles) must be coupled with the legitimate use of authority by prison officers to avoid the emergence, or expansion, of illegitimate prisoner governance. When this does not exist, such peer-support roles can distort the system of power and stimulate, rather than arrest, greater decline in social and moral order.